Multiple Sclerosis: A Brief Overview of the Disease, Its Pharmacotherapy - Aayushi Jaiswal (International Journal of Brain Sciences, 2024)
Multiple Sclerosis is an autoimmune disorder mostly affecting individuals aged between 20-40. In this disorder, the optic, vertebral, and central nervous system nerves are primarily impacted. It is a neurological condition that worsens over time and is characterized by inflammation and the breakdown of the sheath that surrounds and shields the nerve fiber. Common symptoms may include muscle weakness, numbness, tingling, fatigue, vertigo, tremor, vision complications, pain, Lhermitte sign, sexual dysfunction, muscle spasms, bladder problems, and bowel problems. Myelin around the axon composes White matter. Therefore in Multiple Sclerosis Lesions are formed around white matter. Generally, Autoreactive B-cells play an important role in Multiple Sclerosis. Many drugs are available which are used to slow or decrease the progression of but not cure the disease. Various drugs like Ocrelizumab (The MuSicalE STUDY), Bruton Tyrosine Kinase Inhibitor-Evobrutinib, Clemastine (ReBUILD STUDY), Ibudilast, and MD1003(biotin), are under trial which shows their action by acting on various target sites like B-cell, Oligodendrocytes, Toll-like receptor Macrophage migration, Acetyl Co-A carboxylase.
Keywords: Clinically isolated Syndrome; Lhermitte sign; Malonyl Co-A; Relapse-Remitting Multiple Sclerosis